ASPEK PAJAK PENGHASILAN FINAL PADA SEKTOR USAHA MIKRO KECIL DAN MENENGAH (STUDI KASUS PT PCT TANGERANG) - murifal, Badar (Universitas Bina Sarana Informatika, 2019)
AbstractIndonesia cut the final income tax rate for small and medium-sized enterprises by half, to 0.5 percent of their annual sales, in a move to help businesses manage their cash flow and expansion. While the current arrangement only demands simple accounting, small and medium-sized enterprises say it also means they have to pay income tax when they are at loss, which disrupts their cash flow(Jakarta Globes, 2018). The Government has shown its strong support for the development of small and medium enterprises (SMEs). After improving the tax facility for venture capital companies who invest in SMEs, the Government has now issued Government Regulation (GR) No.23/2018 (GR-23) which stipulates a new “final tax”rate for SMEs. GR-23 will enter into force on 1 July 2018 and revokes GR No.46/2013 regarding final tax on taxpayers within a certain turnover. The final tax regime, introduced in GR-46, is applicable for taxpay ers with annual gross turnover of not more than IDR 4.8 billion (approximately USD 340 thousand), excluding the following income: a.fees from the delivery of certain freelance services by individuals; b. overseas income which has been taxed in the source country; c. income also subject to final tax; and d. non - taxable income. The threshold of IDR 4.8 billion per annum is based on the previous years’ activity, including gross turnover sourced from branches. If during a fiscal year the gross turnover exceeds IDR 4.8 billion, the taxpayer remains subject to final tax for the current year but must adopt the “ normal tax ” rate (Article 17 or Article 31E Income Tax) for the following year. While the provisions on gross turnover generally remain unchanged, GR – 23 now reduces the final tax rate to 0.5% from the previous 1%.Key words : Final Income Tax , Micro, Small and Medium Enterprises.